“Holy Water”: The Ritual Praxis of Aladura Churches and Its Economic Implications in South West, Nigeria - Akindolie, Akinwumi Ambrose (Transformation, 2024)
Water is a vital natural resource for every living organism. Water is used for various anthropogenic purposes as drinking, washing, and cooking. In African and non-African religions, water is important for religious practices such as baptism, ablution, cleansing, healing, and worship of gods, to mention but a few. Aladura Churches in Nigeria also use water as one of the natural resources, to facilitate the completion of their rituals. Previous academic works show that the use of water in Aladura Churches is laden with symbolic use and these previous works are noticeable on the spiritual dimensions but neglect its economic implications. This study also argues that water is not only anthropogenic but has elements of sacralization in the ritual and idiosyncrasies of Aladura Churches. The data were gathered through ethnographical methods, interviews, and observation.